Suppression of Carrageenan- and Collagen II-Induced Inflammation in Mice by Geranium Oil - Naho Maruyama; Hiroko Ishibashi; Weimin Hu; Shinichiro Morofuji; Shigeharu Inouye; Hideyo Yamaguchi; Shigeru Abe (Hindawi Limited, 2006)
To obtain experimental evidence on the therapeutic efficacy of essential oils in aromatherapy for inflammatory diseases, we examined the effects of geranium oil on carrageenan-induced and collagen II-induced inflammation in mice, to assess acute and chronic anti-inflammatory activities of the oil. Single intraperitoneal injection of 5 μL of geranium oil clearly suppressed the carrageenan-induced footpaw edema and increase in tissue myeloperoxidase activity, and repeated administration of the oil suppressed collagen-induced arthritis. These results revealed that geranium oil suppressed both acute and chronic inflammatory responses in mice.